Activisme en ligne et transformations sociopolitiques au Burkina Faso - Lassané Yameogo (Communication)
The author analyzes how new tools that allow regular people to speak up and participate in public debates, i.e., digital platforms, can be used to track the emerging digital public arena, public opinion, and democracy in a country that has long been considered to be under a semi-authoritarian regime: Burkina Faso. The results show how online activism and sociopolitical crises are closely related and reveal a reconfiguration of journalism and the emergence of an alternative public arena that is becoming a barometer of governance, but also a vector for the spread of antisocial values.